An evaluative study of the impact of intervention strategies of non- governmental organisations (NGOS) on social well-being, economic empowerment and health of the aged in Oyo state, Nigeria (2006)
The world is aging at an alarming rate and thge aged all over the world are facing a lot of health, social and economic problems. It is against this background that the present study examines the impact of NGO's intervention strategies on social well-being, economic empowerment and health well-being of the aged in Oyo State. The sample comprised 264 old people randomly drawn from four old people's home run fry non-governmental organizations. Four instruments were used: Intervention strategies of NGOs were measured fry sell constructed scale- "Intervention Strategies Scales of NGOs ", Social well-being was assessed by the adapted scale of "Multidimensional Scale of Perceived Social Support" (MSPSS: Zimet et al., 1988); Economic empowerment of the aged was assessed by self constructed scale tagged, "Measurement of Economic Empowerment scale"; Health Well-being was measured by the adapted scale of "Personal Resource Questionnaire"( PRQ) 85 (Carol Roth 2003). Findings showed that NGO's intervention strategies (emotional, information and economic) predicted positively and significantly to the social welI-being (F = 191.7; P < 0.05); economic empowerment (F = 61. 774; p < 0.05) and health well-being (F = 94.601) of the aged. It was recommended that these strategies be sustained for the aged so as to produce aged that have longevity of life and yet remain productive both at the home front and within the community.